2022
DOI: 10.3389/fonc.2022.1038890
|View full text |Cite
|
Sign up to set email alerts
|

ZHX2 in health and disease

Abstract: As a transcriptional factor and the negative regulator of alpha fetal protein (AFP), Zinc fingers and homeoboxes 2 (ZHX2) has a well-established role in protection against hepatocellular carcinoma (HCC). However, recent studies have suggested ZHX2 as an oncogene in clear cell renal cell carcinoma (ccRCC) and triple-negative breast cancer (TNBC). Moreover, mounting evidence has illustrated a much broader role of ZHX2 in multiple cellular processes, including cell proliferation, cell differentiation, lipid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Furthermore, the regulation mediated by PPAR, influencing thyroid peroxidase, thyroglobulin, and thyrotropin receptor gene promoters, facilitates the intricate process of thyroid cell differentiation [44]. These insights shed light on the intricate interplay between signaling pathways and genetic alterations, offering valuable perspectives into the molecular landscape of THCA pathogenesis [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The tumor microenvironment has garnered recognition as a crucial determinant influencing tumor initiation, progression, treatment response, and prognosis [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the regulation mediated by PPAR, influencing thyroid peroxidase, thyroglobulin, and thyrotropin receptor gene promoters, facilitates the intricate process of thyroid cell differentiation [44]. These insights shed light on the intricate interplay between signaling pathways and genetic alterations, offering valuable perspectives into the molecular landscape of THCA pathogenesis [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The tumor microenvironment has garnered recognition as a crucial determinant influencing tumor initiation, progression, treatment response, and prognosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing ACTN1 expression has been demonstrated to impede the proliferation of hepatocellular carcinoma (HCC) [ 31 ]. ZHX2, recognized as a tumor suppressor gene, orchestrates lipid metabolism regulation, suppresses cell proliferation [ 32 ], and influences the immune microenvironment [ 33 ]. Notably, ZHX2 has been implicated in the occurrence of brain metastasis in THCA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence shows that ZHX2 is an important regulator of various biological processes, including regulating the development of various cancers such as liver cancer, gastric cancer, and thyroid cancer, and participating in lipid metabolism, cell differentiation, and development, NK cell maturation, and macrophage cell polarization, etc (33). Many literatures have reported that ZHX2 has an inhibitory effect on the proliferation and migration of different types of cells (17,21,(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the VHL loss of tumor suppressor gene VHL in ccRCC resulted in the accumulation of ZHX2 protein in the nucleus and the subsequent decrease in patient survival rate [ 13 , 15 ]. More importantly, Li et al identifies ZHX2 acting as an oncogenic driver in ccRCC where hypoxia-inducible factors (HIF1 and HIF2) are deregulated [ 16 ]. ZHX2 drives proliferation, migration, colony formation and invasion via activating multiple proteins including Twist, Snail, VEGF, MEK, ERK 1/2 [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%